Study of RF-excited Diethylene Glycol Dimethyl Ether Plasmas by Mass Spectrometry - Algatti, M. A. [UNESP]; Mota, Rogério Pinto [UNESP]; Moreira Junior, P. W. P. [UNESP]; Honda, Roberto Yzumi [UNESP]; Kayama, M. E. [UNESP]; Kostov, K. G. [UNESP] (Iop Publishing Ltd, 2012)
This paper deals with the study of the fragmentation process of diethylene glycol dimethyl ether (CH3O(CH2CH2O)(2)CH3) (diglyme here in) molecule in low pressure RF excited plasma discharges. The study was carried out using mass spectrometry. The results showed that for a fixed pressure, the increase of the RF power coupled to the plasma chamber from 1 to 35 W produced a plasma environment much more reactive which increases the population of the ionized species like CH3+ (15 amu), C2H4+ (28 amu), CH3O+ (31 amu), C2H4O+ (44 amu), CH3OCH2CH2+ (59 amu) and CH3OCH2CH2O+ (75 amu). This fact may be attributed to the increase of the electronic temperature that makes predominant the occurrence of inelastic processes that promotes molecular fragmentation. For a fixed value of RF power the increase of pressure from 50 mTorr to 100 mTorr produces the decreasing of the above mentioned chemical species due the lower electronic mean free path. These results suggest that if one wants to keep the monomer's functionality within the plasma deposited films resulting from such kind of discharges one must operate in low power conditions.